CRIMINATION AS A LAST EFFORT IN A CHILD CRIMINAL JUSTICE SYSTEM REFLECTING THE PRINCIPLE OF RESTORATIVE JUSTICE - Winarno, Jatmiko; Tjahjani, Joejoen; Rochmawanto, Munif; Imam Putri, Intan Dwika (Universitas Islam Lamongan, 2022)
Abstraction Diversion aims to achieve peace between victims and children, resolve cases of children outside the judicial process, prevent children from deprivation of independence, encourage the community to participate and instill a sense of responsibility in children. Diversion must be carried out at every stage starting from the level of investigation, prosecution and examination at the District Court. Diversion is said to be successful if there is an agreement, and the case can be stopped and restorative justice is achieved, whereas if the diversion is not successful then the case is continued until the child is sentenced.